Fertility and Family Leave Policies in Germany: Optimal Policy Design in a Dynamic Framework - Hanna Wang (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
I develop and estimate a life-cycle discrete-choice model of fertility and female labor supply to study the optimal design of a range of child-related policies. First, I examine two German reforms that introduced wage-contingent parental leave payments and expanded access to low-cost public childcare. I find that both reforms raised completed fertility, with the parental leave reform having a particularly strong impact on highly educated women. Second, I solve for a budget-neutral optimal policy portfolio that maximizes either aggregate welfare or fertility, while ensuring that welfare and fertility do not decline for any education group. I consider four prominent child subsidies as well as the degree of tax jointness. My results show that optimal policy has the potential to increase welfare by 0.5% or fertility by 5.7%. While the solutions are qualitatively similar, they prioritize different policy instruments depending on the specific objective being targeted.
Keywords: H21; J13; J24; 330; fertility; parental leave; childcare subsidies; optimal policy